Blobs in a Solar EUV Jet - Chen, Jie; Erdélyi, Robertus; Liu, Jiajia; Deng, Yuanyong; Dover, Fionnlagh Mackenzie; Zhang, Qingmin; Zhang, Mei; Li, Leping; Su, Jiangtao (Frontiers in Astronomy and Space Sciences, 2022)
An Extreme Ultraviolet (EUV) jet that occurred around 22:30 on July 2, 2012 was observed by the Atmospheric Imaging Assembly (AIA) on-board the Solar Dynamics Observatory (SDO). There were two phases of the jet. In Phase 1, two blobs were observed. In Phase 2, the intensity of the jet was almost coherent initially. One minute later, three blobs were formed at the same time in the jet, and the width of the jet changed after the formation of these blobs. The formation and evolution processes of the blobs in these two phases are analyzed in this paper. The physical parameters of the blobs are determined. The measured width of the blobs is $0.8 - 2.3$ Mm, and the apparent velocities of the blobs are from 59 km s$^{-1}$ to 185 km s$^{-1}$. The formation mechanism of the blobs is likely to be tear-mode instability..